IMPLEMENTASI PEMBELAJARAN TEMATIK PADA KURIKULUM 2013 BAGI SISWA KELAS RENDAH DI SEKOLAH DASAR NEGERI 4 SINGOTRUNAN BANYUWANGI - Kulzum, Putri Maja Mulia (IJIT: Indonesian Journal of Islamic Teaching, 2019)
Thematic Learning is approaching in learning directly combine several aspects including lesson intramata or between each lesson. In this learning students will get knowledge and ability fully so the learning become useful for students, they will be able to understand the concept that is learned by them through direct experience. Thematic learning focuses at process that is passed by students when they are trying to understand the content of learning based on the shapes of ability that must be developed. Elementary school 4 Singotrunan Banyuwangi is a school that is used curriculum 2013 that become model school, it proven by getting the first rank Subdistrict Banyuwangi, Tryout of District, Tryout K3S. The purpose of this research are: (1) Describing paradigm of thematic learning at curriculum 2013 for low class at elementary school 4 Singotrunan Banyuwangi. (2) Describing prosses thematic learning at curriculum 2013 for low class at elementary school 4 Singotrunan Banyuwangi. (3) Describing model of thematic learning at curriculum 2013 for low class at elementary school 4 Singotrunan Banyuwangi